PERSEPSI MASYARAKAT TERHADAP DAMPAK KEBERADAAN PERUSAHAAN PERKEBUNAN KELAPA SAWIT DI DESA KACUNG KECAMATAN KELAPA KABUPATEN BANGKA BARAT - Iwan Setiawan; Siti Kafsiah; Evahelda Evahelda (Journal of Integrated Agribusiness, 2021)
PT Bumi Permai Lestari (PT.BPL) which has a total area of 14,319.08 Ha is the largestplantation company in Bangka Barat Regency where one of its branches is located inKacung Village, Kelapa District, Bangka Barat Regency. Several studies have shown thatthe existence of oil palm plantation companies has an impact on the communities wherethe companies are located. Unfortunately, there is no research that shows the impact of theexistence of a plantation company owned by PT Bumi Permai Lestari (PT.BPL) based oncommunity perceptions in Kacung Village, Bangka Barat Regency. The purpose of thisstudy was to analyze people's perceptions of social and economic changes and todetermine the factors that influence people's perceptions of social and economic changesdue to the existence of oil palm plantation companies. The research was conducted inKacung Village from January 2019 to July 2019 using the survey method. A total of 93people in Kacung Village were used as samples using Simple Random Sampling. Theresearch data was processed using a Likert Scale and Binary Logistics Regression. Theresults showed that the people of Kacung Village thought that the existence of PT BumiPermai Lestari (PT.BPL) had a good impact on the social and economic aspects of thecommunity with social and economic indexes of 62% and 66%, respectively. In addition,from the social aspect, the results of the study indicate that the variables of the number offamily members, type of work and social status have a significant effect on publicperception in assessing the impact of the existence of PT.BPL. Meanwhile, from theeconomic aspect, the variables that have a significant effect on people's perceptions inassessing the impact of the existence of PT.BPL are the number of family members, type ofwork, social status and education level